Effect of Abdominal Binding on Diaphragmatic Neuromuscular Efficiency, Exertional Breathlessness, and Exercise Endurance in Chronic Obstructive Pulmonary Disease - Abdallah, Sara J.; Smith, Benjamin M.; Wilkinson-Maitland, Courtney; Li, Pei Zhi; Bourbeau, Jean; Jensen, Dennis (Frontiers in Physiology, 2018)
We tested the hypothesis that abdominal binding (AB) would reduce breathlessness and improve exercise tolerance by enhancing neuromuscular efficiency of the diaphragm during exercise in adults with chronic obstructive pulmonary disease (COPD). In a randomized, controlled, crossover trial, 20 adults with COPD (meanSD FEV1, 6016%predicted) completed a symptom-limited constant-load cycle endurance exercise test at 75% of their peak incremental power output with concomitant measures of diaphragmatic electromyogram (EMGdi) and respiratory pressures without (CTRL) vs. with AB sufficient to increase end-expiratory gastric pressure (Pga,ee) by 6.7±0.3 cmH2O at rest. Compared to CTRL, AB enhanced diaphragmatic neuromuscular efficiency during exercise (p<0.05), as evidenced by a 25% increase in the quotient of EMGdi to tidal transdiaphragmatic pressure swing. By contrast, AB had no demonstrable effect on exertional breathlessness and exercise tolerance; spirometry and plethysmography-derived pulmonary function test parameters at rest; and cardiac, metabolic, breathing pattern, inspiratory reserve volume and EMGdi responses during exercise (all p>0.05 vs. CTRL). In conclusion, enhanced neuromuscular efficiency of the diaphragm during exercise with AB was not associated with relief of exertional breathlessness and improved exercise tolerance in adults with COPD. Clinicaltrials.gov identifier: NCT01852006.